Global Council on Brain Health: Recommendations to promote brain health through music enrichment: Prevention (nonpharmacological) / Other. (7th December 2020) - Lock, Sarah Lenz; Chura, Lindsay Rachel; Parkes, David; ,
Abstract: Background: The Global Council on Brain Health (GCBH) is an independent collaborative of scientists, clinicians, scholars, and policy experts convened by AARP to provide evidence‐based advice on what people and professionals can do to maintain and improve brain health. The Council translates scientific research into actionable recommendations for the public that will help drive behavior change in individuals across communities and cultures. In 2020, the Council will focus on the topic of music specifically as it relates to brain health. Music offers natural and accessible strategies for older adults who wish to exercise their full creative potential or cope with issues related to dysfunction or isolation. Method: Experts from around the world were brought together to analyze the body of evidence on the impact of music and brain health, build consensus, and issue recommendations. AARP's original research captures data from surveys highlighting adult engagement with music as it relates to their brain health. Result: This presentation will feature consensus on whether and how music impacts cognitive health. Recommendations and practical tips based on the latest research advancements will also be showcased to help the public understand the potential that music holds for supporting and enriching brain health. Data from surveys fielded by AARP research, developed in consultation with the GCBH, will be featured. Conclusion: This presentation highlights findings from the Council's examination of the impact of music on brain health. Music and dance/movement interventions can positively impact health outcomes, including cognition, quality of life, psychological impact, mental well‐being, etc. Participation in music therapy and experiences can regulate stress and arousal, thus affecting overall health. The scientific and policy dimensions of music and brain health on aging adults will also be addressed.